A Propaganda Index for Reviewing Problem Framing in Articles and Manuscripts: An Exploratory Study - Gambrill, Eileen; Reiman, Amanda (PloS one, 2011)
To determine the effectiveness of an index in increasing recognition of misleading problem framing in articles and manuscripts. A propaganda index consisting of 32 items was developed drawing on related literature. Seventeen subjects who review manuscripts for possible publication were requested to read five recent published reports of randomized controlled trials concerning social anxiety and to identify indicators of propaganda (defined as encouraging beliefs and actions with the least thought possible). They then re-read the same five articles using a propaganda index to note instances of propaganda. Convenience sample of individuals who review manuscripts for possible publication and sample of recent published reports of randomized controlled trials regarding social anxiety in five different journals by different authors, blinded by author and journal. Data showed that there was a high rate of propagandistic problem framing in reports of RCTs regarding social anxiety such as hiding well argued alternative views and vagueness. This occurred in 117 out of 160 opportunities over five research reports. A convenience sample of 17 academics spotted only 4.5 percent of propaganda indicators. This increased to 64 percent with use of the 32 item propaganda index. Use of a propaganda index increased recognition of related indicators. However many instances remained undetected. This propaganda index warrants further exploration as a complement to reporting guidelines such as CONSORT and PRISMA.